The effect of human platelet lysate on corneal nerve regeneration. Issue 6 (20th November 2019) - Huang, Chin-Te; Chu, Hsiao-Sang; Hung, Kuo-Chi; Chen, Lily Wei; Chen, Mei-Yun; Hu, Fung-Rong; Chen, Wei-Li
Abstract : Aim: This study aimed to test whether human platelet lysate (HPL) has neurotrophic ability for corneal nerve regeneration. Methods: We measured the neurotrophic factors in human peripheral serum (HPS) and two commercially available HPLs, UltraGRO and PLTMax. In vitro, we compared the growth rates, neuronal differentiation and immunostaining of neuron markers in mouse neuroblastoma cell line (Neuro-2a) and primary culture of mouse trigeminal ganglion cells that were cultivated in different concentrations of fetal bovine serum, HPS and HPL. In vivo, we created corneal wounds on Sprague Dawley rats with a rotating burr and evaluated the effects of topical HPL on wound healing and corneal nerve regeneration by in vivo confocal microscopy and corneal aesthesiometry. Results: HPLs had significantly higher concentrations of various neurotrophic factors compared with HPS (p<0.05). In Neuro-2a cells, 3% HPL was better at promoting neuronal growth and differentiation compared with HPS at the same concentration. HPL was also found to have superior neurotrophic effects compared with HPS in primary cultures of mouse trigeminal ganglion cells. In vivo, HPL-treated eyes had better corneal epithelial wound healing rate, nerve regeneration length and corneal touch threshold compared with eyes treated with artificial tears (p<0.05). Conclusion: HPL has significantly higher concentrations of neurotrophic factors compared with HPS. It showed not only in vitro but also in vivo corneal neurotrophic abilities. Our results suggest that HPL may have a potential role in the treatment of diseases related to corneal nerve damage or degeneration.